A reprodução capitalista no setor habitacional e as transformações no espaço urbano: o caso do Jardim Letícia (Leme-SP) - Orsi, Rafael Alves [UNESP] (My University, 2013)
This paper discusses urban space focusing on the housing sector, the capitalist reproduction and some changes occurring in that space as a result of the dynamics of the real estate sector and interests of financial agents, developers and urban land owners/speculators. The changes imposed to cities value abstract spaces over concrete ones, showing the unbalance between the interests of agents, who have in view the market, and those of dwellers, who live daily in such areas. Based on these reflections, a case study was carried out in the Jardim Letícia neighborhood in Leme city (state of São Paulo) in order to understand the space production and reproduction in that area, analyze some of the main problems faced by local people, and identify some agents involved in the process.

O presente trabalho discute o espaço urbano focando o setor habitacional, a reprodução capitalista e algumas das transformações nesse espaço, decorrentes da dinâmica imobiliária e dos interesses de agentes financeiros, incorporadores e proprietários/especuladores de terra urbana. As mudanças impostas às cidades valorizam o espaço abstrato em vez do concreto, o que mostra o descompasso entre os interesses dos agentes, voltados para o mercado, e os dos moradores, que vivenciam cotidianamente esse espaço. Com base nessas reflexões, foi desenvolvido um estudo de caso no bairro Jardim Letícia na cidade de Leme-SP a fim de compreender a produção e a reprodução do espaço nesse bairro, analisar alguns dos principais problemas criados para a população local e identificar alguns dos agentes envolvidos nesse processo.
The capitalist reproduction in the housing sector and the urban space changes: the case of Jardim Letícia (Leme-SP)
Keywords: Dwelling; Urban space reproduction; Urban dynamics; Habitação; Reprodução do espaço urbano; Dinâmica urbana